2021
DOI: 10.1111/ctr.14260
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota profiles and fecal beta‐glucuronidase activity in kidney transplant recipients with and without post‐transplant diarrhea

Abstract: Post‐transplant diarrhea is a common complication after solid organ transplantation and is frequently attributed to the widely prescribed immunosuppressant mycophenolate mofetil (MMF). Given recent work identifying the relationship between MMF toxicity and gut bacterial β‐glucuronidase activity, we evaluated the relationship between gut microbiota composition, fecal β‐glucuronidase activity, and post‐transplant diarrhea. We recruited 97 kidney transplant recipients and profiled the gut microbiota in 273 fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…4.4 mg free phenolphthalein/mg protein/h, P = .78). 26 A significantly greater percentage of diarrheal patients with high β-glucuronidase activity (91%) had a prolonged course (≥7 days) of diarrhea, while only 40% of low β-glucuronidase-activity patients had a prolonged course. 27 In a murine study, exposure to MMF resulted in an altered microbial community composition with increased β-glucuronidase activity that was ablated when vancomycin was given.…”
Section: To the Editormentioning
confidence: 93%
“…4.4 mg free phenolphthalein/mg protein/h, P = .78). 26 A significantly greater percentage of diarrheal patients with high β-glucuronidase activity (91%) had a prolonged course (≥7 days) of diarrhea, while only 40% of low β-glucuronidase-activity patients had a prolonged course. 27 In a murine study, exposure to MMF resulted in an altered microbial community composition with increased β-glucuronidase activity that was ablated when vancomycin was given.…”
Section: To the Editormentioning
confidence: 93%
“…Treatment for ACR included escalation of baseline immunosuppression, steroid pulse (oral or intravenous), or a combination of the above and did not differ between the two groups studied (p = 0.17). Median number of biopsies at 1 month post-HT was similar between the groups (4[4] vs. 4[4], p = 0.20), while at 6 months post-HT there were fewer biopsies in the MMF-LD compared with the MMF-HD group (9[7][8][9] vs. 10 [10], p < 0.01). Median number of biopsies stratified by year is shown in FigureS6.Cumulative 6-month freedom from ACR (≥1R/1B) was not significantly different in MMF-HD and MMF-LD groups (59.2% MMF-HD vs. 70.8% MMF-LD, p = 0.16; Figure3B).…”
mentioning
confidence: 91%
“…Consequently, changes in the intestinal flora, particularly pathogens carrying β‐ d ‐glucuronidases (GUS), may influence the pharmacokinetics of MMF 8 . Recently, other authors found elevated fecal GUS activity in a subset of kidney transplant recipients to be associated with protracted post‐transplant diarrhea 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortage of β-glucuronidase in body tissues consequently results in proliferation of GAGs inside the lysosomes, leading to the enlargement of their size . As a consequence of over-expression of this enzyme in various cancers like the neoplasm of bladder, liver cancer, and colon carcinoma, , the quantitative measurement of β-glucuronidase has been proved as a detection tool at the initial stage diagnosis of cancer and the assessment of therapeutic treatments. , Moreover, it is evident from the literature that an elevated level of β-glucuronidase in blood serum is related to various physiological disorders such as urinary tract infection, rejection of transplantation, epilepsy, renal diseases, rheumatoid arthritis, and larynx and breast cancer . Besides these, acquired immune deficiency syndrome (AIDs) and hepatic disorders have also been reported as a consequence of a high level of this enzyme. , …”
Section: Introductionmentioning
confidence: 99%